Pengaruh Good Corporate Governance dan Ukuran Perusahaan Terhadap Penghindaran Pajak pada Perusahaan Properti dan Real Estate yang Terdaftar di BEI Periode 2020–2023 - Rista, Rara Ayu Anda; Novalita, Novalita; Sari, Meita Sekar; Alie, Maria Septijantini (CV. ULIL ALBAB CORP, 2024)
The aim of this research is to determine the effect of good corporate governance and company size on tax avoidance in property and real estate companies listed on the IDX for the 2020-2023 period. The sampling technique uses a purposive sampling technique with a multiple linear regression analysis approach. The data used in this research is secondary data obtained from financial reports of property and real estate companies for 2020-2023. The research results show that good corporate governance and company size partially influence tax avoidance. Independent commissioners have an effect on tax avoidance, audit committees have no effect on tax avoidance, company size has no effect on tax avoidance.